2016
DOI: 10.3389/fnins.2016.00427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceftriaxone on Glial Glutamate Transporters in Wistar Rats Administered Sequential Ethanol and Methamphetamine

Abstract: Methamphetamine (METH) is one of the psychostimulants that is co-abused with ethanol. Repeated exposure to high dose of METH has been shown to cause increases in extracellular glutamate concentration. We have recently reported that ethanol exposure can also increase the extracellular glutamate concentration and downregulate the expression of glutamate transporter subtype 1 (GLT-1). GLT-1 is a glial transporter that regulates the majority of extracellular glutamate. A Wistar rat model of METH and ethanol co-abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…Likewise, no change in GLT-1 in midbrain, NAc, dorsal striatum, or PFC is reported following amphetamine sensitization ( Sidiropoulou et al, 2001 ). Repeated high doses of methamphetamine (10 mg/kg x 4, every 2 hours) decrease GLT-1 in striatum and hippocampus ( Althobaiti et al, 2016 ). The disparity between these results likely reflects differences in dosing and treatment regimens.…”
Section: Eaat2/glt-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, no change in GLT-1 in midbrain, NAc, dorsal striatum, or PFC is reported following amphetamine sensitization ( Sidiropoulou et al, 2001 ). Repeated high doses of methamphetamine (10 mg/kg x 4, every 2 hours) decrease GLT-1 in striatum and hippocampus ( Althobaiti et al, 2016 ). The disparity between these results likely reflects differences in dosing and treatment regimens.…”
Section: Eaat2/glt-1mentioning
confidence: 99%
“…Ceftriaxone reduces drug-induced reinstatement of methamphetamine and nicotine CPP ( Abulseoud, 2012 ) ( Alajaji et al, 2013 ). Likewise, ceftriaxone reduces physical, somatic, and affective nicotine withdrawal signs in ICR mice ( Alajaji et al, 2013 ) and nicotine intake in female P rats ( Sari et al, 2016 ). Subthreshold doses of MK-801, an NMDAR antagonist, plus ceftriaxone reduce the acquisition of morphine CPP and block extinction and reinstatement of preference ( Fan et al, 2012 ).…”
Section: Translational Studies On Eaat Pharmacotherapies For Addictiomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chronic ethanol drinking was shown to decrease GLT-1 and xCT expression in the NAc (Alhaddad et al, 2014; Das et al, 2015b). Therefore, CEF treatment decreased ethanol intake and upregulated GLT-1 in the NAc and PFC (Alhaddad et al, 2014; Althobaiti et al, 2016b; Sari et al, 2011; Sari et al, 2013). CEF’s upregulatory effect on GLT-1 expression is suggested to be mainly attributed to the β-lactam ring found in this drug and other β-lactam antibiotics (Rothstein et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Studies from ours and others have reported that GLT-1 was downregulated in the NAc following exposure to several drugs of abuse, including ethanol and cocaine (Ginsberg et al, 1995, Danbolt, 2001, Knackstedt et al, 2009, Sari and Sreemantula, 2012, Fischer et al, 2013, Shen et al, 2014). Importantly, a study from our laboratory showed that sequential exposure to ethanol and repeated high dose methamphetamine caused additive downregulation of GLT-1 in the NAc than either drug exposed alone (Althobaiti et al, 2016). …”
Section: Introductionmentioning
confidence: 99%